Observation of coherent Cherenkov diffraction radiation modes in a long cylindrical Teflon radiator; Radiation Physics and Chemistry; Vol. 240 - Grigoryan L. Sh. Levon; Potylitsyn A. P. Alexander Petrovich; Karataev P. V. Pavel Vladimirovich; Dabagov S. B. Sultan Barasbievich; Kubankin A. S. Aleksandr Sergeevich; Kidanova E. Yu. Elena Yurjevna; Antonov V. N.; Vukolov A. V. Artem Vladimirovich; Kishin I. A.; Cherepennikov Yu. M. Yuriy Mihaylovich; Shevelev M. V. Mihail Viktorovich; Grigoryan B. A.; et al. (2026, 2026)
Title screen